Enhancement of microbubble mediated gene delivery by simultaneous exposure to ultrasonic and magnetic fields. - Stride, E; Porter, C; Prieto, A; Pankhurst, Q (2009)
It has been shown in previous studies that gene delivery can be enhanced by a variety of minimally-invasive techniques including: (1) exposure of cells to ultrasound in the presence of DNA and gas microbubbles and (2) exposure of cells to a magnetic field in the presence of DNA conjugated to magnetic nanoparticles. The aim of this work was to investigate whether it was possible to combine the advantages of both these techniques. It was found that transfection of Chinese hamster ovary cells by naked plasmid DNA was enhanced by combined exposure of the cells to ultrasound (10 s at 1 kHz pulse repetition frequency with 40 cycle 1 MHz sinusoidal pulses, 1 MPa peak to peak pressure) and a magnetic field (provided by five square cross-section N52 grade NdFeB magnets 25 x 10 x 10 mm with transversal magnetisation Br = 1.50 T arranged in a Halbach array), in the presence of one of two different microbubble/nanoparticle preparations. The first preparation consisted of phospholipid coated microbubbles mixed with micelles containing magnetic nanoparticles. The second consisted of microbubbles which were themselves magnetically active. These preparations were found to be more effective than either magnetic micelles or phospholipid coated microbubbles alone by a factor of 2.8 (total flux approximately 4 versus 1.4 x 10(6) photon/s) and the results were found to be statistically significant (p < 0.01). Two mechanisms are proposed to explain these observations: firstly, that the magnetic field facilitates close proximity between the cells and the microbubbles and hence increases the likelihood of transfection; second, that there is sensitisation of the cells, as a result of exposure to the magnetic field in the presence of the micelles, which increases their ability to be transfected upon exposure to ultrasound. Further work is in progress to determine which of these mechanisms is the most significant and the potential for other therapeutic applications.